PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN ZOOM DALAM PEMBELAJARAN TERHADAP HASIL BELAJAR EKONOMI SISWA KELAS X SMA SWASTA YPK MEDAN TA.2021/2022 - Intan Purnama Sari; Cita Ayni Putri Silalahi (Jurnal Inovasi Penelitian, 2022)
This study aims to determine the effect of using zoom learning media on the learning outcomes of class X students at YPK Private Senior High School Medan. This type of research uses quantitative research by distributing questionnaires and tests with a sample of 40 students of class X SMA Private YPK Medan. In accordance with the hypothesis that the author formulated in this study, it was as follows: "Is there any influence on the use of Zoom Learning Media in learning on Economic Learning Outcomes of Class X Students of YPK Private High School Medan TA. 2021/2022". From the results of this study, it can be seen that the two variables have a significant influence between zoom learning media on economic learning outcomes. With regression coefficient constant value a= 1.05 and b= -0.28. Thus the equation of a simple linear line is Y = 1.05+-0.28X. In this case b is positive, it can be concluded that student learning outcomes (variable Y) increased by -0.28. And based on the results of hypothesis testing using the formula, it shows that the value of t_(count) is 0.20 while the magnitude of t_(table) at a significant level of 5% with dk = n-2 = 40-2= 38 is 1.68. Because t_hitung t_table or 0.20 1.68 then the formulation of the hypothesis that has been set in this study can be accepted as true, it can be concluded that: "there is a positive and significant effect between Zoom on student learning outcomes in economics learning in class X SMA Private YPK Medan T.A 2021/2022.